Ecological specialisation and range size determine intraspecific body size variation in a speciose clade of insect herbivores. Issue 9 (30th June 2022) - Seifert, Carlo L.; Strutzenberger, Patrick; Fiedler, Konrad
Abstract : The body size of an adult insect is strongly determined by the environmental factors to which it is exposed during growth and development. Insect species confronted with a high environmental variability across their geographical range (i.e. wide ecological niche breadth) may therefore reveal broader variation in body size than those species which are more specialised (i.e. narrow ecological niche). In this study, we aim to investigate whether characteristics related to the ecological niche breadth of a holometabolous insect species (i.e. its ecological specialisation) affect its intraspecific variation in adult body size. By using European geometrid moths as a model group, we specifically tested whether latitudinal range size, larval resource use and voltinism affect intraspecific body size variation. We hypothesised that body size variation will increase along with latitudinal range and larval diet breadth. We further expected that univoltine species reveal a lower body size variation compared to those with multiple generations per year. To test these hypotheses, we compiled a comprehensive trait database for 631 species of European geometrid moths from literature, including information on adult body size, life history and distribution. We further reconstructed a molecular phylogeny including all analysed geometrid species and applied phylogenetic comparative methods in order to test our predictions. In support of our hypotheses, we found that intraspecific size variation is positively related to latitudinal range size and larval diet breadth, and that multivoltine species reveal a higher heterogeneity in body size than taxa with a strictly univoltine life style. Based on our results, we demonstrated that intraspecific body size variation in geometrid moths is negatively related to ecological specialisation. We further suggest that increased variation in body size with increasing niche breadth is a general pattern, which likely applies to many other insect groups as well. This assumption, however, demands further empirical scrutiny.